PERBANDINGAN MODEL KINERJA STRUKTUR TAHAN GEMPA DENGAN WILAYAH BERBEDA MENGGUNAKAN METODE RESPON SPEKTRUM - Pribadi, Gali Pribadi; Faizal Addin Achmad (Fakultas Teknik Universitas Krisnadwipayana, 2023)
Indonesia is an earthquake-prone area, many earthquakes that occur in Indonesia cause damage to building structures in Indonesia. The planning rules for building a building are that the building must be able to withstand existing earthquake loads. Because basically the principle of earthquake-resistant buildings is that damage to the building may occur, but not to structural elements This research takes a case study of a 19-storey apartment building. This building has a height of 62.7 meters with a total of 19 floors. According to SNI 1726: 2019 regulations, the function of this building is shown as a residential facility with risk category II. The results of the analysis are in the form of building structure performance, comparison between Jayapura and Jakarta soil data, level deviation and column and brace stress control